Exploring the Mathematical Education of Teachers Using TEDS-M Data - Tatto, Maria Teresa; Rodriguez, Michael C.; Smith, Wendy M.; Reckase, Mark D.; Bankov, Kiril (Springer International Publishing : Imprint: Springer, 2018)
XXIV, 579 p. 40 illus.